KAITAN INTENSITAS HAMBURAN SINAR GAMMA TERHADAP SIFAT FISIS BATUAN - Sitorus, Merryana Desidoria; Natalisanto, Adrianus Inu; Lepong, Piter (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2018)
Information on the intensity of gamma-rays scattered by the rock formation is contained in the density-log which is the output of a well logging system. In this research it was studied the relation of the intensities with the physical properties of the rocks in a rock formation. The study was performed by determining the intensities of gamma-rays scattered recorded in the data of density-log’s curves and continued by analyzing the rock’s physical properties that might decrease the intensities of gamma rays, such as molecular weight, coefficient of attenuation, and scattering cross-sectional. Result of the research was the graph which can be used to predict the properties of any sediment rocks by only using the scattered gamma ray intensities recorded in the data of density log.